Effect of fermentation time and temperature on butanol production from palm oil mill effluent (POME) by using Clostridium Acebutylicum - Siti Nadiah, Mustafa Kamal (2010)
Malaysia is the world’s largest producer of palm oil. Waste from palm oil production factories has been increasing rapidly and one of the serious problems in the palm oil fruit processing is the managing of the waste generated by the processes. Recently, fermentative energy production from several sources of biomass has been carried out which is Acetone–butanol–ethanol (ABE) fermentation (Shinto et al., 2008). Due to this, this study is focusing on the utilization of palm oil mill effluent (POME) for ABE fermentation by Clostridium acetobutylicum (NCIMB 13357). The main objective of this study is to develop conversion of POME into useful material which is butanol. Investigations were carried out on the effects of fermentation temperature within 35°C to 45°C and fermentation time within 48 to 72 hours to the butanol production. The experiment were conducted in Schott bottle with 90% concentration of culture medium and 10% v/v of inoculums concentration by using POME and reinforced clostridia medium (RCM) as growth medium. This anaerobic fermentation was done in batch culture. It was observed that the optimum condition for butanol fermentation by C.acetobutylicum is at 40°C through 48 hours which produced the highest yield of butanol (3.1344 g/L). From this study, it showed that the butanol production was decreased as the fermentation temperature and time were increased. The results from this study hence showed that the POME is a viable media for butanol fermentation. For improvement, research on other parameter such as pH of substrate and concentration of substrate that effect on butanol production should be carried out to optimize the production of butanol.